Effects of Cassava-Based Feed on Growth and Physical Performance of Broilers - Daniel, Ebiakpo Lucky; Ukpong, Inibehe George; Saviour, Jonah (International Journal of Agriculture System, 2025)
The study was carried out to assess the effects of cassava-based feed on the growth and physical performance of broilers. Fifty-one (51) day-old broiler chicks were used for the experiment. The birds were divided into two experimental groups; the first group had 25 chicks, and the second group had 26 chicks and was allotted two dietary treatments. Treatment A contained 50% cassava, 50% leaf meal, 50% maize, and 50% fresh soya bean, while Treatment B contained 100% cassava root meal and 100% cassava leaf meal. At the end of the eight-week experiment, Treatment B (birds fed 100% cassava root meal and cassava leaf meal, referred to as CSV/FM—Cassava Stem/Root meal and Fish Meal) had comparably lower mortality of 3 birds than Treatment A, which recorded 17 mortality cases. Treatment B also has a comparably higher body weight and mean weight gain than birds in Treatment A. The birds fed in Treatment B were observably more agile and more active, with comparatively excellent eating rate. The choice of cassava as an alternative to feed components follows that cassava is relatively cheaper, most commonly available in Southern Nigeria, than other routinely used feed supplements such as maize. Thus, to reduce the cost and high demand for conventional feedstuffs, especially maize, as a significant source of energy in poultry nutrition, up to 100% cassava, combined with fish meal as a common ingredient, can be used to replace maize and fresh soya bean in broiler chickens’ diets. When properly processed, cassava root meal can replace maize (as an energy source), and cassava leaf meal can partially replace soybean meal (as a protein source) in livestock diets, particularly for broilers and fish. Thus, up to 100% cassava could replace maize in broiler chicken diets to reduce the feed cost.